PRAGMATICS TEACHING BARRIERS IN EFL CLASSROOM - Berutu, Hotma; Daulay, Sholihatul Hamidah (Universitas PGRI Sumatera Barat, 2023)
Pragmatics is a branch of linguistics that study about language and its context. In learning a second language, EFL learners need to have a pragmatic competence in order to be able to communicate effectively based on the context of the target language. There are some factors that can help learners improve their pragmatic competence, not only the EFL teachers who are competent in their field but also the tools and media that support the learning process. This study aimed to investigate (1) what the most common barriers to teaching pragmatics in EFL classrooms by Indonesian EFL teachers and (2) how pragmatic norms is provided in textbooks by the Indonesian authors. Qualitative used as the research methodology in this study. The participants of this study were 15 Indonesian EFL teachers from different schools – junior and senior high schools. The writer used questionnaire as the instrument research. The participants were given questionnaires to find out what exactly the barriers found to teaching pragmatics in EFL classroom. English textbooks used in junior and senior high school written by Indonesian authors were also analyzed by the researcher. This study came up with the findings that (1) there are six common barriers to teaching pragmatics in EFL classroom by Indonesian EFL teachers and (2) most of the ELT textbooks do not consider the pragmatic norm in its content. Given the significance of students' pragmatic abilities, EFL teachers need to keep improving their research of teaching pragmatics in order to help EFL learners in developing their pragmatic competence.